Sleep and Control of Breathing 2021
DOI: 10.1183/13993003.congress-2021.pa2080
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the novel coronavirus (COVID-19) pandemic on sleep

Abstract: Background: The COVID-19 pandemic has led to significant changes in daily routines and lifestyle worldwide and mental health issues have emerged as a consequence. We aimed to assess the presence of sleep disturbances during the lockdown in the general population.Methods: Cross-sectional, online survey-based study on adults living through the COVID-19 pandemic.The questionnaire included demographics and specific questions assessing the impact of the pandemic/ lockdown on sleep, daytime functioning and mental he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 3 publications
1
18
0
Order By: Relevance
“…The effect of COVID-19 pandemic on sleep patterns has been confirmed by many studies 5 6 14 22–24. Although studies were conducted among different geographical and ethnic societies, with people of different ages and occupations, the common conclusion was that the SARS-CoV-2 pandemic affects sleep quality by changing subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, daytime dysfunction and by causing sleep disturbances and usage of sleeping medication 6 13 22–24. Our study results were in line with the results of the study by Yuksel et al that was conducted across 59 countries and confirmed increased sleep disturbances during the COVID-19 pandemic, with their different distributions among different gender groups, age groups and marital status 5…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The effect of COVID-19 pandemic on sleep patterns has been confirmed by many studies 5 6 14 22–24. Although studies were conducted among different geographical and ethnic societies, with people of different ages and occupations, the common conclusion was that the SARS-CoV-2 pandemic affects sleep quality by changing subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, daytime dysfunction and by causing sleep disturbances and usage of sleeping medication 6 13 22–24. Our study results were in line with the results of the study by Yuksel et al that was conducted across 59 countries and confirmed increased sleep disturbances during the COVID-19 pandemic, with their different distributions among different gender groups, age groups and marital status 5…”
Section: Discussionsupporting
confidence: 90%
“…The effect of COVID-19 pandemic on sleep patterns has been confirmed by many studies 5 6 14 22–24. Although studies were conducted among different geographical and ethnic societies, with people of different ages and occupations, the common conclusion was that the SARS-CoV-2 pandemic affects sleep quality by changing subjective sleep quality, sleep latency, sleep duration, habitual sleep efficiency, daytime dysfunction and by causing sleep disturbances and usage of sleeping medication 6 13 22–24.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The COVID‐19 pandemic has affected sleep and dreams for many individuals and has been linked to changes in mental health, lifestyle habits and social interactions (Pérez‐Carbonell et al, 2020; Shillington et al, 2021). Insomnia severity during this time has been linked to suicide ideation (Killgore et al, 2020) and much of the anxiety and stress associated with health and general well‐being has played out in dreams and nightmares with pandemic‐related themes (Guerrero‐Gomez et al, 2021; MacKay & DeCicco, 2020; Mota et al, 2020; Ruby, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Sleep disturbances in older adults have been well‐documented during the COVID‐19 pandemic 1 . Recent studies have found significant changes in sleep complaints and sleep architecture during the pandemic, including a 37% increase in rates of insomnia, 2 changes in sleep duration and time spent during each sleep stage, 3 changes in sleep patterns, and difficulty achieving refreshing sleep 4 . Data from previous natural disasters and acutely stressful events (e.g., 9/11 terrorist attack, Oklahoma City bombing) show that subjectively‐measured sleep disturbance is common in response to stress 5 .…”
Section: Introductionmentioning
confidence: 99%